USING STIMULATED RECALL METHOD IN UNDERSTANDING TEACHER INTERACTIVE DECISION MAKING - Risna Saswati (STBA LIA - Jakarta, 2018)
This study sheds lights on whether Stimulated Recall (SR) as data collection method can gain accurate information if the recall is not conducted immediately after the task is completed. This study emerges from a research conducted previously about teacher decision making regarding their language use which is a dissertation writing and is not published yet. This paper is to investigate whether it is applicable to recall thought processes of teacher interactive decision making. This study applies interpretative method which uses documents of classroom observation video transcription and post observation interview transcription as data. The result is it is beneficial to use SR as data collection method since it can gain information accurately to recall the thought processes of teacher interactive decision making. It can work well to collect the data if SR is conducted based on the recommendations proposed by Gass and Mackay (2000) which are time, strong stimulus, good training for the research participants, and consistency with research questions.